The Relationship between Affective and Continuance Organizational Commitment - Chien-Hung, Lin; Wen-Cheng, Wang (Journal of Asian Business Strategy, 2012)
Organizational commitment was measured by Organizational Commitment Questionnaire (OCQ) which consists of two scales: an affective commitment scale and a continuance commitment scale. This study used quantitative methodology to examine the relationship between affective and continuance organizational commitment. Subjects of this study were the employees in Taiwanese hotels. In order to collect primary data, subjects completed a questionnaire containing the measure of their feelings of their employing hotel. Data collected from respondents were analyzed using statistical methods. This study indicates that affective commitment is not an important factor that influences an employee’s level of continuance commitment.